Transformation of the cognitive sphere of "digital generation" children: Experience analysis - Lilia A. Belozerova; Sergey D. Polyakov (Saratov State University, 2021)
The article studies the problem of changes in the cognitive sphere of children and adolescents of the digital generation - "generation Z" - in the context of influence of socio-cultural processes and digital technologies on the human psyche. We analyse data and models of changes in perception, thinking, memory and attention in the process of transformation of the socio-cultural situation. Arguments are given in favor of the standpoint emphasizing the ambiguous nature of the influence of digital technologies on the cognitive development of a modern person. The study has pointed out that this ambiguity is manifested both through the deficit in the development of "classical" cognitive mechanisms, and in the generation of new cultural tools (according to L.S. Vygotsky) that help a young person to adapt to the reality of the modern socio-cultural situation. We raise the problem of correlating the language of "classical" psychology of cognitive processes and cognitive characteristics of young people, which are observed in new linguistic forms. Furthermore, we consider the thesis regarding consideration of psychological characteristics of "generation Z" as a relatively universal one. It is argued that the data on modern adolescents cited in the studies should be interpreted as features of the most sensitive part of the birth cohort to the "digital onset". We consider the place of the given analysis in solving the problem of education individualization in relation to psychological and pedagogical characteristics of adolescents, described as "generation Z", and modern educational technologies.